Vigilance in human groups: A test of alternative hypotheses - Dunbar, R; Cornah, L; Daly, F; Bowyer, K (2002)
Humans exhibit the same inverse relationship between group size and vigilance rates that has been classically described in animals. We collected data on natural human vigilance behaviour in two different contemporary environments (a large refectory-style cafeteria and open parks) to test between four alternative hypotheses for this relationship: predation risk, searching for friends, mate searching and mate guarding. The results demonstrate that, at least in contemporary city environments, humans monitor their surroundings largely for reasons motivated by mate searching. Data on whom subjects look at in a busy environment indicate that males are significantly more likely to attend differentially to female passers-by, but that females show a less clear-cut discrimination. We conclude that vigilance patterns are determined by locally salient functions.